HUBUNGAN ANTARA KOMPONEN PERMUKIMAN DAN KEBERHASILAN METODE BANK SAMPAH DALAM PENGELOLAAN SAMPAH BERKELANJUTAN DI KOTA SURAKARTA - Mohamad Nuriman; Soedwiwahjono Soedwiwahjono; Rufia Andisetyana Putri (ARSITEKTURA, 2015)
Garbage was one of the environmental problems. As time goes by, garbage has become that cause new problems like water pollution, air pollution, flood and others. Most of people seeing garbage as unused items that cannot work and then system of garbage management by government did not function properly. Today begins to develop a sustainable garbage management with community role to managing garbage. One of the part of sustainable garbage management is garbage bank method. In sustainable garbage management method particularly with garbage bank must be adjusted and considered by environmental conditions local settlements in order to successful, the aspect related to housing components such as physical environment, economy, community, law, culture and the availability of utilities have an important relation in the development  of sustainable garbage management.This research wants to know what is relationship between housing components and success of garbage bank method on sustainable garbage management, and the next step is identfy housing components and success of garbage bank in two area, RW IX Kelurahan Kadipiro and RW II Kelurahan Gajahan with scoring analyse and finally do the crosstab analyse to determine the relationship between both of them. The conclusion is a housing components with individual aspect such as nature, society, shell and network have important relation with the success of garbage bank  method. This research is to identfy the housing components and success of garbage bank method in two case studies, so we can determine the relationship between both of them in RW IX Kelurahan Kadipiro and RW II Kelurahan Gajahan, Surakarta. Keywords: sustainable garbage management, garbage bank, housing components